2022
DOI: 10.3390/cells11111834
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelial-to-Mesenchymal Transition in Cardiovascular Disease

Abstract: Endothelial-to-mesenchymal transition (EndoMT) is the process of endothelial cells progressively losing endothelial-specific markers and gaining mesenchymal phenotypes. In the normal physiological condition, EndoMT plays a fundamental role in forming the cardiac valves of the developing heart. However, EndoMT contributes to the development of various cardiovascular diseases (CVD), such as atherosclerosis, valve diseases, fibrosis, and pulmonary arterial hypertension (PAH). Therefore, a deeper understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 153 publications
0
30
0
Order By: Relevance
“…During this process, the endothelial cells lose their endothelial characteristics, and begin to express mesenchymal markers (13,14,16,17,21). The transition is a continuum, and endothelial cells undergoing EndMT co-express both endothelial and mesenchymal markers (13,18,19). While there are hallmarks of early and late EndMT, studies have shown this can vary depending on the pathological environment and cell type (14)(15)(16)18,19).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During this process, the endothelial cells lose their endothelial characteristics, and begin to express mesenchymal markers (13,14,16,17,21). The transition is a continuum, and endothelial cells undergoing EndMT co-express both endothelial and mesenchymal markers (13,18,19). While there are hallmarks of early and late EndMT, studies have shown this can vary depending on the pathological environment and cell type (14)(15)(16)18,19).…”
Section: Discussionmentioning
confidence: 99%
“…While there are hallmarks of early and late EndMT, studies have shown this can vary depending on the pathological environment and cell type (14)(15)(16)18,19). Additionally, cells can undergo partial or full EndMT transition, further complicating detection of EndMT transition (13,18,19). An important regulator of EndMT is Snail1, a transcription factor known to induce EndMT (13,22,17,19,20,(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations